Indirect Tensile Fatigue Test (ITFT) Analysis of Asbuton Mixture with Used Oil Additives and HDPE - M Ari Husni; I Dewa Made Alit Karyawan; IAO Suwati Sideman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to assess the impact of the use of used oil and High Density Polyethylene (HDPE) plastic as additives in asphalt mixtures modified with Asbuton on fatigue resistance in AC-BC mixtures. This mixture is designed with an optimal asphalt content of 6.0% and combined with variations in the proportion of modified Asbuton asphalt and oil asphalt. Testing was carried out using the Indirect Tensile Fatigue Test (ITFT) method at a pressure of 500 kPa and at a temperature of 20 degrees Celsius to evaluate fatigue performance due to repeated loads. The results showed that increasing the proportion of modified asphalt containing Asbuton, used oil, and HDPE resulted in a significant increasing trend in the fatigue life of the tested specimens. These findings indicate that asphalt modification with a combination of these waste materials can increase the flexibility and resistance of the mixture to repeated loads. This study contributes to the development of more environmentally friendly road pavement materials with better performance.